AiCoBM 2024: advancing global dialogue in business and management - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
The 4th AAGBS International Conference on Business Management (AiCoBM 2024) was successfully held, marking another significant milestone in AAGBS's commitment to advancing global discourse in business, management, and leadership. The conference brought together academics, industry leaders, policymakers, and international partners to engage in meaningful discussions on navigating uncertainty, innovation, and sustainable business strategies in a rapidly changing global environment. AAGBS extends its sincere appreciation to its strategic partners, Yamaguchi University (Japan) and Cardiff University (United Kingdom), as well as its valued collaborators, UiTM Perpustakaan Tun Abdul Razak (PTAR) and Penerbit UiTM, whose strong support contributed greatly to the successful organisation of the conference. The School also gratefully acknowledges the generous sponsorship of FWD Takaful Berhad and Maybank Islamic, which played a vital role in enhancing the overall quality and impact of the event. AiCoBM 2024 was further strengthened by the presence of distinguished keynote speakers who brought diverse perspectives from academia and industry. Tan Sri Bashir Ahmad Abdul Majid, Chairman of Mass Rapid Transit Corporation (MRT Corp) Malaysia, delivered a compelling keynote on "Navigating Uncertainty: Strategies for Thriving in the Dynamic Business Landscape," offering strategic insights on leadership and resilience in times of disruption.